INCIDENCIA DE DENGUE Y SU RELACIÓN CON FACTORES EPIDEMIOLÓGICOS EN LA RED DE SALUD SAN MARTÍN, DURANTE LOS AÑOS 2017 – 2020 - Laury Silva, Karla (2023)
In Peru, the epidemic outbreak of Dengue produced in 1990 in the Amazon zone affected 25% of the population; The circumstances for the spread of the Dengue virus are ideal and the vector takes advantage of these, since it is widely disseminated in 385 districts. This problem is increasing for public health in the tropical areas of Peru, dengue is currently considered the most important viral disease that is transmitted by mosquitoes and affects humans. Objective: To measure the incidence and epidemiological factors have a direct relationship with Dengue disease in the San Martin Health Network, during 2017 - 2021 Methodology: Corresponds to a descriptive, quantitative, retrospective, cohort and design study correlational. Results: The incidence is 7%, a temperature between 18°C and 33°C, with a rainfall intensity of 156 mm/month. The review of the analyzes carried out in this report shows that there is a direct relationship with some epidemiological factors favoring the transmission of Dengue Disease. Conclusions: The incidence is medium level and there is a direct relationship with environmental, time and social factors.